Comparison of the United States and Indonesia Mathematics Curriculum: Analysis of Structure, Implementation, and Challenges - Ahmad Rizal Saqibul Fiqri; Stevanus Budi Waluyo; Mulyono Mulyono (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
This article examines a comparative analysis of mathematics curricula in the United States and Indonesia, focusing on their structural design, implementation practices, and the challenges encountered in practice. This study employs a literature review method by analyzing official curriculum documents, scholarly articles, policy reports, and empirical studies published within the last five years. The analysis shows that the United States implements a standardized curriculum through the Common Core State Standards for Mathematics (CCSSM), which emphasizes coherence across grade levels and a balance between conceptual understanding, procedural fluency, and mathematical application. Meanwhile, Indonesia’s Merdeka Curriculum adopts a more flexible phase-based structure to accommodate diverse educational contexts. In practice, the United States benefits from stronger infrastructure, professional development, and consistent assessment systems, whereas Indonesia faces challenges related to disparities in facilities, teacher readiness, and varying levels of understanding of Learning Outcomes and authentic assessment. The synthesis indicates that curriculum effectiveness is strongly influenced by alignment between structural design, implementation capacity, and policy stability. This article provides valuable insights for strengthening mathematics curriculum development across diverse educational settings